Civil war outcomes and a durable peace: setting the record straight - Joakim Kreutz (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
One strand of current conflict research claims that military victories are beneficial for peace. It is argued that these outcomes produce more unified post-conflict societies, thereby facilitating reconstruction and economic development. The implication of this view is that, instead of encouraging negotiated settlements, international actors should either support one side to victory or allow a conflict to run its course. This briefing paper argues that the case for “peace by victory” is weaker than supporters claim. The most successful conflict resolutions address their root causes and involve a broad range of stakeholders. A quick glance at all civil war terminations since 1946 seems to suggest that military victories are slightly more stabilizing than other outcomes. Rough comparisons, however, are insufficient for drawing conclusions or offering policy advice. A full review of the context and content of peacebuilding reveals a very different picture. Focusing only on military victories and peace agreements ignores the most common outcome of civil strife: an ongoing contest between belligerents, albeit with a limited use of force. On average, the civil wars that ended with peace agreements lasted eight times longer than those that were terminated through a military victory. Indeed, a one-sided victory almost only occurs when fighting is counted in days or months rather than years. This indicates that protracted conflicts are unlikely to end if allowed to run their course and that negotiations are the only way to end a long-running war. Differences in conflict duration mean that the challenges for reconstruction are substantially greater after negotiated settlements than after military victories. International actors seeking to contribute to the rebuilding that follows peace agreements are faced with societies with more victims and divisions, and greater physical destruction. Regardless of how a conflict ended, the most important factor for post-conflict stability is the orderly demobilization of former fighters. After a war, it is also imperative for the underlying grievances to be addressed through non-violent policies such as offering the vanquished side the opportunity to form a political party and/or share power in the government. Long-term success in conflict management calls for dismantling troop mobilization structures as well as those used for repression. This includes ensuring that both the army and militias return to the barracks and come under official civilian control. External actors can best contribute by helping to create outlets where grievances can be aired and addressed peaceably. Although it is very important to reduce violence quickly, armed belligerents must not be seen as the sole representatives of conflicting views. The following recommendations can be drawn from this paper: – Talks about the issues are the only realistic outcome of a protracted conflict. – Conflict negotiations should not only involve the violent parties but also other non-violent, legitimate stakeholders. – While peace negotiations must be held in a central location, local efforts to promote intra-societal trust also need to be initiated and supported. Many potential peace-process spoilers are less concerned with the terms of a national agreement than with their immediate local security.
Keywords: 330; Sicherheit; Frieden und fragile Staaten